Lead with a story : a guide to crafting business narratives that captivate, convince, and inspire - Smith, Paul, 1967 July 3- (American Management Association, 2012)
Forget facts, figures, and PowerPoint slides-well-crafted stories deliver business concepts simply and powerfully.